Given \(P(x) = 3x^{4} - 5x^{3} + x^{2} - 3x + 5\)

\(Q(x) = (((3x - 5)x + 1)x-3)x+5\)

\(R(x) = x^{5} -2x^{4} + 3x^{3} - 2x^{2} + 3x + 4\)

Expand Q

\(Q(x) = (((3x - 5)x + 1)x-3)x + 5\)

\(=((3x^{2} - 5x + 1)x-3)x + 5\)

\(=(3x^{3} - 5x^{2} + x - 3)x + 5\)

\(= 3x^{4} - 5x^{3} + x^{2} - 3x + 5\)

\(\text{So}, P(x) = Q(x) = 3x^{4} -5x^{3} +x^{2} - 3x + 5\)

Hence proved

Step 2

Evaluate P(2) and Q(2)

\(P(x) = 3x^{4} - 5x^{3} + x^{2} - 3x + 5\)

\(P(2) = 3(2)^{4} - 5(2)^{3} + (2)^{2} - 3(2) + 5\)

\(= 48 - 40 + 4 - 6 + 5\)

\(=11\)

\(Q(2) = (((3(2) - 5)2+1)2- 3) 2 + 5\)

\(=((3(2) + 1)2 - 3)2 +5\)

\(=((3(2) - 3)2 + 5\)

\(= (3)2+5\)

\(= 11\)

Nested form of R(x)

\(R(x) = x^{5} - 2x^{4} + 3x^{3} - 2x^{2} + 3x +4\)

\(R(x) = (x^{4} - 2x^{3} + 3x^{2} - 2x + 3)x +4\)

\(= ((x^{3} - 2x^{2} + 3x - 2)x + 3)x +4\)

\(= (((x^{2} - 2x + 3)x - 2)x + 3)x +4\)

\(= ((((x - 2)x + 3)x - 2)x + 3)x +4\)

\(R(x) = ((((x - 2)x + 3)x - 2)x + 3)x +4\)

\(R(3) = ((((3 - 2)3 + 3)3 - 2)3 + 3)3 + 4\)

\(=167\)